Skunk Works, 1990s-Style - Gwynne, Peter
Peter Gwynne reports that today's skunk works provide role models for entire companies.
Skunk works provide large technology companies with the opportunity to compete on a level playing field against smaller competitors. But they require careful preparation if they are to pay off.
In the effort to keep up with smaller, more nimble competitors, large high-technology companies are increasingly turning to skunk works-small groups of scientists, engineers and other personnel who tackle specific problems and try to commercialize the solutions. However, no skunk works comes with a guarantee. Cases in which skunk works have failed to deliver illustrate the factors necessary for success. The corporate culture must be appropriate to support a countercultural entity in its midst. At least one top manager must support the nascent skunk works and insulate its personnel from day-to-day corporate activities. And management must devise a strategy for commercializing the result of the skunk works activity.